Strategic Management of Psychological Contract Breach in the Gig Economy: Evidence from Grab Indonesia - Raziki Waldan; Johari Bin Abdullah (AKTIVA: Journal of Accountancy and Management, 2026)
Research Purpose: This study aims to identify and analyze the impact of psychological contract breach (PCB) on the performance and job satisfaction of driver-partners at PT. Grab, Pontianak Perdana Branch.Method: The research method used was in-depth interviews with company management and driver-partners.Research Finding: The results indicate that PCB occurs due to a discrepancy between the initial promises made by the company regarding incentives and bonuses and the reality experienced by the driver-partners. The primary factors contributing to PCB include ineffective communication, poorly communicated policy changes, and inadequate technical support. PCB has a significant negative impact on the motivation and performance of driver-partners, as evidenced by decreased productivity and a high level of complaints.Novelty: The implications of this study highlight the importance for companies to enhance communication transparency, maintain consistency in policies, and improve technical support and safety assurance programs. The novelty of this research lies in its focus on a tech startup in a city with an industrial development that differs from other major cities in Indonesia, namely Pontianak.  Tujuan Penelitian: Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis dampak pelanggaran kontrak psikologis (Psychological Contract Breach/PCB) terhadap kinerja dan kepuasan kerja mitra pengemudi di PT. Grab Cabang Perdana Pontianak. Metode: Metode penelitian yang digunakan adalah wawancara mendalam dengan manajemen perusahaan dan mitra pengemudi.Temuan Penelitian: Hasil penelitian menunjukkan bahwa PCB terjadi akibat ketidaksesuaian antara janji awal perusahaan terkait insentif dan bonus dengan kenyataan yang diterima oleh para mitra pengemudi. Faktor utama yang menyebabkan PCB adalah komunikasi yang kurang efektif, perubahan kebijakan yang tidak disosialisasikan dengan baik, dan dukungan teknis yang kurang memadai. PCB berdampak negatif signifikan terhadap motivasi dan kinerja mitra pengemudi, yang ditunjukkan melalui penurunan produktivitas dan tingginya tingkat keluhan.Kebaruan: Implikasi dari penelitian ini adalah pentingnya perusahaan untuk meningkatkan transparansi komunikasi, konsistensi dalam kebijakan, serta memperbaiki dukungan teknis dan program jaminan keselamatan kerja. Kebaruan penelitian ini terletak pada fokusnya pada perusahaan startup teknologi di kota dengan perkembangan industri yang berbeda dari kota besar lainnya di Indonesia, yaitu Pontianak.